A Review and Comparison of Floating Offshore Wind Turbine Model Experiments. (September 2016) - Stewart, Gordon; Muskulus, Michael
Abstract: Floating offshore wind turbines provide more access to deeper water than conventional fixed-bottom wind turbines, which expands the viable area for wind energy development, reduces visibility from shore, and can potentially be located in areas with a higher and steadier wind characteristic. However, since floating turbines are in the early prototype stage of development, there are very limited data to use for validating computer models of these machines. This lack of validation increases uncertainty and risk for future installations. In lieu of large scale test turbines, which are expensive to build and operate, a few institutions have conducted small scale experiments in wave basins. This paper will present a review of the past and planned model-scale floating offshore wind turbine experiments, with a focus on types of data collected and challenges encountered by these tests. The objective of this review is to provide a background for the Integrated Research Program on Wind Energy (IRPWind), specifically for Work Packages 6.1 and 6.2. The goal of these work packages is to create a database of both fixed-bottom and floating offshore wind turbine test cases that can be accessed by researchers to verify and validate computer-aided engineering codes. The database will consist of a number of benchmarks that will validate different parts of a given design code. This review will discuss two model experiments that are likely to be included in the IRPWind database.